Regenerative braking energy utilization system for electrified railways based on energy scheduling between substations - LYU Shunkai (机车电传动)
It will contribute to the energy saving and green development of railways by means of strengthening the research and application of regenerative braking energy utilization technology. In order to realize the direct and efficient use of regenerative braking energy, based on the principle of mutual scheduling use of regenerative braking energy between substations, a kind of regenerative braking energy utilization system for electrified railway that composed of an energy management device and an energy scheduling device was designed. Taking into account multiple constraints, including the traction load demand, regenerative braking energy, system rated power, preset scheduling threshold and so on, an optimal control strategy was proposed. Finally, comprehensive on-site tests were carried out through demonstration project. The test results show that the system design is reasonable, the control strategy is correct and feasible, and the regenerative braking energy utilization rate reaches 62.5%, which meets design expectations.